Country Experiences with the Introduction and Implementation of Inflation Targeting - Otker, Inci (IMF Working Papers; Working Paper ;, 2009)
This is the tenth chapter of a forthcoming monograph entitled, "On Implementing Full- Fledged Inflation-Targeting Regimes: Saying What You Do and Doing What You Say." It describes the experiences of a number of countries with the introduction and implementation of inflation targeting regimes. It discusses their motivation for introducing IT; how they fared in meeting the various conditions that some have argued are needed in advance of introducing IT; how they transitioned to a full-fledged IT framework and coordinated their preparations with other economic policies and reforms; the benefits they gained by adopting IT; the challenges they faced in implementation; and the lessons from their experiences.